Corporate Governance and Shariah Compliance with Fraud Financial Statements at Sharia Commercial Banks: Corporate Governance dan Shariah Compliance Terhadap Financial Statement Fraud Pada Bank Umum Syariah - Desiana, Lidia; Alfaridzie, M. Rifky Ramadhon; Akbar, Dinnul Alfian (Journal of Accounting Science, 2021)
This study tested the Influence of Corporate Governance and Shariah Compliance on Financial Statement Fraud in Sharia Commercial Banks in the Period 2015-2019. Independent variables in this study are Corporate Governance and shariah compliance projected with Islamic Income Ratio, Profit Sharing Ratio and Islamic Investment Ratio. While the dependent variable used is Financial Statement Fraud in sharia commercial banks. The population in this study was all Sharia Commercial Banks (BUS). Sampling techniques using purposive sampling method. The number of samples as many as 12 Islamic commercial banks with a lot of data 60. The results of this study show islamic income ratio affects Financial Statement Fraud, while Profit Sharing Ratio, Islamic Investment Ratio and Corporate Governance have no effect on Financial Statement Fraud.